Isolation and Characterization of Antimicrobial Substance from Marine Streptomyces sp. - ROFIQ SUNARYANTO; BAMBANG MARWOTO; TUN TEDJA IRAWADI; ZAINAL ALIM MAS'UD; LIESBETINI HARTOTO (Indonesian Society for microbiology, 2010)
Isolation and purification of antimicrobial active substance produced by marine Actinomycetes has been carried out. Marine sediment samples were obtained from six different places at Banten West Coast. Isolation was conducted using two pretreatment methods, acid and heat shock pre-treatment. A total of 29 Actinomycetes isolates were obtained from the various sediment samples collected, then tested for antimicrobial activity against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC25923, Pseudomonas aeruginosa ATCC27853, Bacillus subtilis ATCC 66923, Candida albicans BIOMCC00122, and Aspergillus niger BIOMCC00134. Among the isolates, isolate A11 was the most activity to Gram-positive and Gram-negative bacteria, and morphological observation and identification using 16S rRNA showed that the isolate was similar to Streptomyces sp. Production of active compound from A11 isolate used yeast peptone medium. Purification of active compounds was carried out using silica-gel-column chromatography and preparative HPLC. A single peak of active compounds was detected by HPLC, which showed a retention time of 8.35 min and maximum absorbance in UV visible at 210 nm and 274.5 nm respectively.